Glycyrrhizic Acid Scavenges Reactive Carbonyl Species and Attenuates Glycation-Induced Multiple Protein Modification: An In Vitro and In Silico Study. (11th October 2021) - Alvi, Sahir Sultan; Nabi, Rabia; Khan, Mohd. Shahnawaz; Akhter, Firoz; Ahmad, Saheem; Khan, M. Salman
Abstract : The current study is aimed at studying the inhibitory effect of glycyrrhizic acid (GA) on D-ribose-mediated protein glycation via various physicochemical analyses and in silico approaches. Being a potent free radical scavenger and a triterpenoid saponin, GA plays a vital role in diminishing the oxidative stress and thus could be an effective inhibitor of the nonenzymatic glycation process. Our data showed that varying concentrations of GA inhibited the in vitro BSA-AGEs via inhibiting the formation of fructosamines, fluorescent AGEs, scavenging protein carbonyl and hydroxymethyl furfural (HMF) content, and protection against D-ribose-induced modification of BSA as evident by increased free Arg and Lys residues in GA-treated Gly-BSA samples. Moreover, GA also attenuated D-ribose-induced alterations in the secondary structure of BSA by protecting the α -helix and β -sheet conformers and amide-I band delocalization. In addition, GA attenuated the modification in β -cross amyloid structures of BSA and in silico molecular interaction study too showed strong binding of GA with higher number of Lys and Arg residues of BSA and binding energy ( Δ G) of -8.8 Kcal/mol, when compared either to reference standard aminoguanidine (AG)-BSA complex ( Δ G: -4.3 Kcal/mol) or D-ribose-BSA complex ( Δ G: -5.2 Kcal/mol). Therefore, GA could be a new and favorable inhibitor of the nonenzymatic glycation process that ameliorates AGEs-related complications via attenuating the AGE formation and glycation-induced multiple protein modifications with a reduced risk of adverse effects on protein structure and functionality; hence, it could be investigated at further preclinical settings for the treatment and management of diabetes and age-associated complications.